-5(p+3/6)=-4

Simple and best practice solution for -5(p+3/6)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(p+3/6)=-4 equation:



-5(p+3/6)=-4
We move all terms to the left:
-5(p+3/6)-(-4)=0
We add all the numbers together, and all the variables
-5(+p+3/6)-(-4)=0
We add all the numbers together, and all the variables
-5(+p+3/6)+4=0
We multiply parentheses
-5p+4-3/6*5=0
We multiply all the terms by the denominator
-5p*6*5-3+4*6*5=0
We add all the numbers together, and all the variables
-5p*6*5+117=0
Wy multiply elements
-150p*5+117=0
Wy multiply elements
-750p+117=0
We move all terms containing p to the left, all other terms to the right
-750p=-117
p=-117/-750
p=39/250

See similar equations:

| w-233=319 | | 1/4|-2-3x|=1 | | 8(w-7)=3w-41 | | 7(1-7y)=-3(y-2) | | 0.4x-1.2=0.15x=0.8 | | 2y+2=100 | | 7x-54=60 | | 2y-4=y+4 | | -0.4+x=0.42 | | -5x+7(x+4)=3x+3` | | -5+7(x+4)=3x+31 | | 6(v-1)-3=-3(-6v+4)-6v | | j-37/(-6)=(-8) | | -0.2+x=0.42 | | -0.2+x=0.4166666 | | f-14/6=8 | | -19.84+12.6k=19.6k+19.36 | | -3x+5=2(-3x=3)+8 | | 4x-2-3=3+12+8 | | -19.5c-14.87=-12.17-19.3c | | -2/5+x=5/12 | | -8z+11=-9z | | 4x-2-3=3+128 | | -19.3c-19.5c-14.87=-12.17-19.3c | | 17+k=-18k-15+11k | | z/7-47=43 | | -19.3c-19.5c-14.87=-12.17 | | z7− 47=-43 | | -x/3+4=7 | | 98=6s+8 | | j/3+12=4 | | 3d-2/2=8d-5/4 |

Equations solver categories